(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless devices that used to measure physiological signals to help develop health management become increasingly popular in recent years. Records are conducive for follow-up health and medical care. Using different type of wireless devices and the factors of a large number of users, large number of data are lead to create a security threads and privacy problems. With the help of wireless technology and cloud computing we may solve the traditional way of problems occurred at the time of data management and data transmission in health management system. This healthcare management application to propose an integrated algorithm technique for the jointly involved parties which is included privacy and security algorithm; it can protect data integrity also. This system provides the better efficiency and it is very useful to remote areas where hospitals are not easily accessible. This research to resolve wireless sensor network security relevant issues Using several patterns can reduce database load, and users to access data efficiently; the privacy control mechanism allow users to store data securely. The results of this research exhibit that the proposed system has better secured database access and maintain privacy for all patient data than the traditional database.